Interest in Using Islamic Bank Payroll Through Perception, Reference Group, and Religiosity - Ade Risa Fitriani Mursidah; Cut Erika Ananda Fatimah (Fakultas Ekonomi, UIN Maliki Malang, 2023)
The university is an educational institution that can positively help the development of Islamic banking. It can be seen from the existence of Islamic banking and Islamic economics majors in the Faculty of Economics and Business. This research aims to analyze the direct and indirect influence between perceptions and reference groups on Interest in using Islamic bank payroll with Religiosity as an intervening variable, a case study at the Faculty of Economics and Business, UIN Jakarta. This study analyzed 70 respondents using quantitative methods and SEM PLS data analysis techniques using SmartPLS. The results of this study indicate that perceptions, reference groups, and Religiosity directly or indirectly influence Interest. This study will explain how perceptions, reference groups, and Religiosity towards interest variables use Islamic bank payroll.